A plasmonic study of electrical field enhancement and nanocircuit theory over nanoparticles and nanoslits - ABBAS, Ghulam (2019)
We begin with the electromagnetic field propagation through nano slit composed of different materials. Field enhancement, plasmonic characteristics and power flow are discussed. An equivalent circuit that can model the nano slit and surrounding medium is purposed. The different combinations used in the slab include, gold-gold, silver-gold and silver-silver. It is assumed that the nano slit is placed in free space. This study focus on the behavior of electromagnetic field at the surfaces. Further, different types of nanocavities are introduced at the entrance of nanoslit to enhance the power flow and electric field. An excellent response is observed to obtain the required goals and new method to build a nanoslit is presented. Next we consider spherical nanoparticles, that were prepared in lab and also analyzed using COMSOL Multiphysics simulations. The comparison between theoretical and experimental results is presented. Nanospheres with and without coating are considered to study the interaction of electromagnetic field with these particles. The nano particles consist of silver or gold and coating layer of SiO₂ or Al₂O₃ are considered. For the case of nanosphere it is assumed that the surrounding medium is water. Using optical properties and parameter values an equivalent circuit for nanosphere is also modeled. In the next step, we focus on nano ellipsoids placed in free space composed of different materials, we analyze the nano ellipsoids and design corresponding equivalent circuit. We consider that the nanoellipsoid consist of silver or gold and the coating layer consist of SiO₂ or Al₂O₃, similarly as we did in the case of nanosphere. Finally, using seed based approach, silver nanoprisms are fabricated and their optical properties are studied. The experimental and simulation results are obtain to compare the response of nanoprism composed of silver and gold. Based on optical properties and using modeling parameters the values of nanocomponents are calculated. The effect of size shape and surrounding medium are discussed by using different types of nanoparticles. Ag and Au NPs were characterized using Uv-Vis, and SEM. The spectra was recorded on Thermo Scientific Evolution 600S spectrophotometer.